Penerapan Sertifikasi Aquaculture Stewardship Council (ASC) Terhadap Produk Udang Budidaya (Studi Kasus: Tarakan - Kalimantan Utara) - Radityo Pramoda; Hertria Maharani Putri (Jurnal Borneo Administrator, 2017)
ASC (Aquaculture Stewardship Council) is a label, indicating that a product that has been passed through environmental sustainability and good aquaculture practices. Objectives of this study are to identify ASC standards and national regulations, and to examine the readiness of exporters and shrimp farmers to apply ASC principles in Tarakan. This study utilizes empirical juridical and descriptive statistical methods. Results of the study indicate that: (1) ASC certification has 7 principles, 34 criteria, and 103 indicators; (2) ASC principles are supported by: 5 Laws, 4 Government Regulations, 1 Presidential Decree, 3 Regulations of the Minister of Marine Affairs and Fisheries, and 4 Decrees of the Minister of Marine Affairs and Fisheries; (3) ASC certification requires high cost; (4) in general the level of readiness of exporter and shrimp fishermen still need to be improved; (5) pond land is mostly illegal. The policy recommendations of this research are: (1) the government reorganizes the national regulatory system to avoid overlapping rules and regulatory vacancies; (2) the government provides lobbies and assessors to relieve the cost of certification; (3) the government adopts the ASC principle criteria to improve competitiveness; (4) the government encourages municipal government in Tarakan to immediately resolve the problem of illegal fishing ponds. Keywords: Application, Cultivation Stewardship Council, Aquaculture Shrimp Products ASC (Aquaculture Stewardship Council) merupakan sebuah label, bahwa produk sudah melalui prosedur keberlanjutan lingkungan dan aspek sosial praktek budidayayang baik. Tujuan penelitian ini adalah mengidentifikasi ketentuan ASC dan regulasi nasional, serta mengkaji kesiapan eksportir maupunpembudidaya Udang menerapkan prinsip ASC di Tarakan.Analisis kajian menggunakan metode yuridis empirisdan statistika deskriptif. Hasil penelitian menunjukkan: (1) sertifikasi ASC memiliki 7 prinsip, 34 kriteria, dan 103 indikator; (2) prinsip ASC didukung: 5 Undang-Undang, 4 Peraturan Pemerintah, 1 Keputusan Presiden, 3 Peraturan Menteri Kelautan dan Perikanan, dan 4 Keputusan Menteri Kelautan dan Perikanan; (3) sertifikasi ASC membutuhkan biaya mahal; (4) secara umum tingkat kesiapan eksportir dan petambak Udang masih perlu ditingkatkan; (5) lahan tambak sebagian besar ilegal. Rekomendasi kebijakan penelitian ini: (1) penataan sistem regulasi nasional untuk menghindari tumpang tindih aturan dan kekosongan pengaturan; (2) pemerintah melakukan lobi atau menyediakan tenaga penilai untuk meringankan biaya sertifikasi; (3)mengadopsi kriteria prinsip ASC untuk meningkatkan daya saing; (4) pemerintah mendorong otoritas daerah Kota Tarakan segera menuntaskan masalah lahan tambak ilegal. Kata Kunci: Penerapan,Aquaculture Stewardship Council, Produk Udang Budidaya